Mature, long-lived CD4+ and CD8+ T cells are generated by the thymoma in myasthenia gravis. - Buckley, C; Douek, D; Newsom-Davis, J; Vincent, A; Willcox, N (2001)
Antibodies to muscle acetylcholine receptors, to other muscle antigens, and to some cytokines are found in the majority of patients with thymic tumors (thymomas) and myasthenia gravis (MG). The role of the tumor in initiating autoimmunity, however, is unclear; in particular, it is not known whether the thymoma exports mature and long-lived T cells, which could provide help for antibody production in the periphery. Here, we quantified recently exported thymic T cells using the approach of measuring episomal DNA fragments [T-cell receptor excision circles (TRECs)], generated by T-cell receptor gene rearrangement. Compared to values in healthy individuals (n = 10) or in patients with late-onset MG (n = 8), TREC levels were significantly raised in both the CD4+ and CD8+ peripheral blood compartments of patients with thymoma and MG (n = 14, p = 0.002 and p = 0.0004 compared to healthy controls) but only in the CD8+ compartment of the three patients with thymoma without MG (p = 0.4 and p = 0.01 for CD4+ and CD8+). TREC levels decreased following thymectomy to values similar to controls but were substantially raised in patients who had developed tumor recurrence (n = 6, p = 0.04 and p = 0.02 for CD4+ and CD8+); this was associated with increased antibodies to interferon-alpha and interleukin-12 in the one case studied serially. Collectively, these results support the hypothesis that the neoplastic thymoma tissue itself can generate and export mature, long-lived T cells and that these T cells reflect the thymic pathology and are likely to be related to the associated autoimmune diseases. The results also provide a new approach for early diagnosis of thymoma recurrence.